Odpowiedź :
Odpowiedź:
a)
[tex]\frac{2}{3} (2x-3)-3=1-\frac{3}{2} \\ \frac{4}{3} x-2-3=1-\frac{3}{2}\\ \frac{4}{3} x=1+5-\frac{3}{2}\\ \frac{4}{3} x=4\frac{1}{2} /*\frac{3}{4} \\ x=4\frac{1}{2} *\frac{3}{4}\\ x=\frac{9}{2} *\frac{3}{4}=\frac{27}{8} =3\frac{3}{8}[/tex]
b)
[tex]\frac{x}{2} -\frac{1}{3} =3-x+\frac{5}{6} /*6\\ 3x-2=18-6x+5\\ 3x+6x=23+2\\ 9x=25/:9\\ x=\frac{25}{9} =2\frac{7}{9}[/tex]
c)
[tex]2x-\frac{1}{2} -3x-\frac{1}{3} =1+x-\frac{1}{4} /*12\\ 24x-6-36-4=12+12x-3\\ 24x-46=9+12x\\ 24x-12x=9+46\\ 12x=55/:(12)\\ x=\frac{55}{12} =4\frac{7}{12}[/tex]
d)
[tex]\frac{2}{3} x-0,75=\frac{1}{2} (x-2)+0,25x\\ \frac{2}{3} x-\frac{3}{4} =\frac{1}{2} (x-2)+\frac{1}{4} x/*12\\ 8x-9=6(x-2)+3x\\ 8x-9=6x-12+3x\\ 8x-3x-6x=-12+9\\ -x=-3/*(-1)\\ x=3[/tex]
e)
[tex]0,4x+\frac{1}{5} =2x-\frac{5}{10} -0,6\\ \frac{4}{10} x+\frac{1}{5} =2x-\frac{5}{10} -\frac{6}{10} /*10\\ 4x+2=20x-5-6\\ 4x+2=20x-11\\ 4x-20x=-11-2\\ -16x=-13/:(-16)\\ x=\frac{13}{16}[/tex]
f)
[tex]0,3(3x-5)+\frac{1}{2} (2-x)=0,2(x-5)\\ \frac{3}{10} (3x-5)+\frac{1}{2} (2-x)=\frac{2}{10} (x-5)/*10\\ 3(3x-5)+5(2-x)=2(x-5)\\ 9x-15+10-5x=2x-10\\ 4x-5=2x-10\\ 4x-2x=-10+5\\ 2x=-5/:2\\ x=-2,5[/tex]
Odpowiedź:
a)
[tex]\frac{2}{3}(2x-3)-3=1-\frac{3}{2}[/tex]
[tex]\frac{4}{3}x-2-3=-\frac{1}{2}[/tex]
[tex]\frac{4}{3}x=2+3-\frac{1}{2}[/tex]
[tex]\frac{4}{3}x=4\frac{1}{2}/:\frac{4}{3}[/tex]
[tex]x=\frac{9}{2}*\frac{3}{4}[/tex]
[tex]x=\frac{27}{8}=3\frac{3}{8}[/tex]
b)
[tex]\frac{x}{2} -\frac{1}{3}=3-x+\frac{5}{6}/*6[/tex]
[tex]3x-2=18-6x+5[/tex]
[tex]3x+6x=23+2\\[/tex]
[tex]9x=25/:9[/tex]
[tex]x=2\frac{7}{9}[/tex]
c)
[tex]2x-\frac{1}{2}-3x-\frac{1}{3}=1+x-\frac{1}{4}[/tex]
[tex]-x-x=\frac{3}{4}+\frac{1}{3}+\frac{1}{2}[/tex]
[tex]-2x=\frac{19}{12}/:(-2)[/tex]
[tex]x=-\frac{19}{24}[/tex]
d)
[tex]\frac{2}{3}x-0,75=\frac{1}{2}(x-2)+0,25x[/tex]
[tex]\frac{2}{3}x-\frac{3}{4}=\frac{1}{2}x-1+\frac{1}{4}x/*12[/tex]
[tex]8x-9=6x-12+3x[/tex]
[tex]8x-6x-3x=-12+9[/tex]
[tex]-x=-3/*(-1)[/tex]
[tex]x=3[/tex]
e)
[tex]0,4x+\frac{1}{5}=2x-\frac{5}{10}-0,6[/tex]
[tex]0,4x-2x=-0,5-0.6-0,2[/tex]
[tex]-1,6x=-1,3/:-1,6[/tex]
[tex]x=0,8125[/tex]
f)
[tex]0,3(3x-5)+\frac{1}{2}(2-x)=0,2(x-5)[/tex]
[tex]0,9x-1,5+1-0,5x=0,2x-1[/tex]
[tex]0,4x-0,2x=-1-1+1,5[/tex]
[tex]0,2x=-0,5/:0,2[/tex]
[tex]x=-2,5[/tex]
Szczegółowe wyjaśnienie: